High-flow oxygen for children's airway surgery: randomised controlled trial protocol (HAMSTER). Issue 10 (14th October 2019) - Humphreys, Susan; von Ungern-Sternberg, Britta Sylvia; Skowno, Justin; Williams, Tara; Taylor, Julia; Taverner, Fiona; Gibbons, Kristen; Burgoyne, Laura; Sommerfield, David; Stephens, Philip; Hallett, Ben; Vijayasekaran, Shyan; et al.
Abstract : Introduction: Hypoxaemia during anaesthesia for tubeless upper airway surgery in children with abnormal airways is common due to the complexity of balancing adequate depth of anaesthesia with maintenance of spontaneous breathing and providing an uninterrupted field of view of the upper airway for the surgeon. High-flow nasal oxygenation (HIGH-FLOW) can prolong safe apnoea time and be used in children with abnormal airways but to date has not been compared with the alternative technique of low-flow nasal oxygenation (LOW-FLOW). The aim is to investigate if use of HIGH-FLOW can reduce the number of hypoxaemic events requiring rescue oxygenation compared with LOW-FLOW. Methods and analysis: H igh-flow oxygen for children's a irway surgery: rando m i s ed controll e d t r ial (HAMSTER) is a multicentre, unmasked, randomised controlled, parallel group, superiority trial comparing two oxygenation techniques during anaesthesia. Children (n=530) aged >37 weeks to 16 years presenting for elective tubeless upper airway surgery who fulfil inclusion but not exclusion criteria will be randomised prior to surgery to HIGH-FLOW or LOW-FLOW post induction of anaesthesia. Maintenance of anaesthesia with HIGH-FLOW requires Total IntraVenous Anaesthesia (TIVA) and with LOW-FLOW, either inhalational or TIVA at discretion of anaesthetist. The primary outcome is the incidence of hypoxaemic events requiring interruption of procedure for rescue oxygenation by positive pressure ventilation and the secondary outcome includes total hypoxaemia time, adverse cardiorespiratory events and unexpected paediatric intensive care admission admission. Hypoxaemia is defined as Sp02 <90%. Analysis will be conducted on an intention-to-treat basis. Ethics and dissemination: Ethical approval has been obtained by Children's Health Queensland Human Research Ethics Committee (HREC/18/QRCH/130). The trial commenced recruitment in 2018. The primary manuscript will be submitted for publication in a peer-reviewed journal. Trial registration number: The HAMSTER is registered with the Australia and New Zealand Clinical TrialsRegistry: ACTRN12618000949280.